A Spotlight on Novel Coronavirus (COVID – 19) with Various Types of Strains: Life Sciences-Microbiology - Biswas, Souvik; Roy, Dipan; Debnath, Biplab; Das, Arijit; Nath, Rajarshi; Nag, Mrinmoy; Boral, Poushali; Biswas, Poulomi; Dewan, Debajit; Pramanick, Nabanita; Sarkar, Utkalika; Chattopadhyay, Souvik; et al. (International Journal of Life Science and Pharma Research, 2022)
Deadly COVID-19 viruses have raised a pandemic situation in the year 2019, causing serious and contagious respiratory infections in humans. SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) is the main causative agent for this disease outbreak. The pandemic created a critical impact on the global economy. The emergence of SARS-CoV-2 in late 2019 was followed by a period of relative evolutionary stasis that lasted about 11 months. Since, late 2020, SARS-CoV-2 evolution has been characterized by the emergence of sets of mutations. This resulted so far, in over 2.7 million deaths and near about 122 million infection cases. Most mutations in the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) genome are either deleterious and swiftly purged or relatively neutral. As far as the concern is the variants it impacts the virus characteristics, including antigenicity and transmissibility in response to the modification of the human immune profile. In recent days, COVID-19 affected cases are rapidly increasing and it became difficult to inhibit this virus as they are continuously mutated in the host cell forming various new strains like B.1.1.7, B.1.351, P.1, P.2, B.1.1.529, etc. These monitoring, surveillance of variation, and sequencing efforts within the SARS-CoV-2 genome enabled the rapid identification of the first some of Variants of Concern (VOCs) in late 2020, where genome changes became the most observable impact on virus biology and disease transmission. In this review article, we tried to focus and spot the light on the genetic diversification of various strains, their nature, similarities and dissimilarities, mechanism of action, and the prophylactic interventions which could prevent this life-threatening disease in the long run.